Endogenous Institutions and the Politics of Property: Comparing and Contrasting Douglass North and Karl Polanyi in the Case of Finance - Davis, Ann E. (Journal of Economic Issues, 2008)
The purpose of this paper is to contrast the work of Douglass North and Karl Polanyi regarding financial institutions associated in market economies. Both implicitly acknowledge the synergy between public and private financial markets, which can serve to solidify an alliance between wealth holders and the state, potentially at the expense of “sociery” at large. This alliance may stimulate growth, according to North, as well as impose the strain of the market, according to Polanyi. Taken together, these insights undercut the classical story of the neutral role of money, as well as the notion of a clear distinction between public and private, politics and markets.
Economics
Keywords: NORTH; Douglass; economic history; finance; property

Affect and the Rise of the Self-Regulating Market - Gammon, Earl (Millennium: Journal of International Studies, 2008)
This article outlines a post-rationalist approach to international political economy that factors in the role of affect in social causation. There are key historical junctures where social transformations cannot be neatly explained by instrumental logics, such as the profit motive or the pursuit of increasing productive efficiency. Affect, in the form of anxiety and aggression, overdetermines social behaviour in ways that belie conventional notions of rationality, premised on a clear ordering of needs or preferences by social actors. This analysis specifically reassesses the role of affect in the rise of market civilisation in Britain in the early part of the nineteenth century. It critiques Karl Polanyi's account, which privileges technology and pecuniary greed as the expedients of the institution of the self-regulating market. As an alternative, this article explains the rise of the self-regulating market as a retributive mechanism, whereby the market became conceived as a means of punishing and disciplining social behaviour in the early Victorian period. The market, I argue, was an aggressive response to anxiety that plagued Victorian society regarding social order, an anxiety precipitated by the waning belief in a natural moral economy guided by the hand of Providence.
Political Science; International Relations
Keywords: Great Britain; affect; critique; international political economy; post-rationalist IPE; self-regulating market; social causation

The Karl Polanyi Institute of Political Economy : A Narrative of Contributions to Social Change - Gomez, Ana (Revue Interventions économiques. Papers in Political Economy, 2008)
Introduction: In February of 1941 Karl Polanyi wrote to his daughter Kari about his intention to submit to the publisher the first three chapters of the book The Great Transformation. The Origins of the Cataclysm. About the book, he wrote “[I]t will be a very straight-forward, simple story, easy to read and mainly historical in character”. A week later he added a post-script. Referring to the Notes in the manuscript, he wrote, “[T]he book is seemingly so simple and unsophisticated that unless d...
N/A
Keywords: Karl Polanyi; double mouvement; double movement; encadrement; marchandise fictive; école substantiviste

Anthropology in the financial crisis - Hart, Keith; Ortiz, Horacio (Anthropology Today, 2008)
This editorial considers the opportunities opened up for anthropologists by the financial crisis of 2008. The chief of these is the exposure of cracks in the intellectual hegemony of free-market economics which contributed to an unnecessarily defensive posture on the part of most anthropologists during the period of neoliberal globalization. The authors claim that anthropology can bridge the gap between everyday life and the world at large by combining the study of ideas and social actions. We draw on Ortiz's research among financial professionals to show how working practices informed by economic liberalism can have extremely unequal consequences for the global distribution of resources. The perspectives of Mauss and Polanyi on political economy can help us to make sense of the current situation and to recommend a path forward beyond market fundamentalism. Their general ideas lend power to the concrete findings of field research. The mask of neoliberal ideology has been ripped from the politics of world economy. Anthropology's highest mission is to start from where people are and go with them wherever they take you. What better time to follow this imperative than when the model the world has been compelled to live by for three decades is in such disarray?
Anthropology
Keywords: finance; financial crisis

Encastrement et nouvelle sociologie économique : de Granovetter à Polanyi et Mauss - Laville, Jean-Louis (Revue Interventions économiques. Papers in Political Economy, 2008)
Le concept d’encastrement s’est imposé dans la nouvelle sociologie économique. Ce texte souligne sa polysémie. Dans une première partie, il rappelle les deux acceptions politique et réticulaire respectivement adoptées par Granovetter et Polanyi. Rapportée à la modernité démocratique, la démarche de Polanyi permet de mettre en évidence un double mouvement caractérisant les rapports entre économie et société, dont les grands traits sont synthétisés dans la deuxième partie. Si l’on adopte une telle lecture, la convergence entre Polanyi et Mauss apparaît alors dans une approche plurielle de l’économie, présentée dans la troisième partie. Selon l’hypothèse esquissée dans la quatrième partie, une telle lecture suggère d’approfondir la teneur des changements institutionnels susceptibles de conforter la pluralité de l’économie, autrement dit de participer à son « ré-encastrement » démocratique. The concept of embeddedness has imposed itself in the New Economic Sociology. This paper highlights the multiple meanings of this term. In a first part, we discuss the political and reticular meanings adopted by Granovetter and Polanyi respectively. In the context of modern democracy, the work of Polanyi shows a double movement characterizing the relations between economy and society, which we develop in the second part. With such a perspective, the convergence between Polanyi and Mauss is highlighted in a plurial approach of the economy, which we discuss in the third part. The hypothesis presented in the fourth part leads us to analyze the content of institutional changes which can confirm the plurality of the economy, and to participate in its democratic « reembeddedness ».
Sociology; Economics
Keywords: GRANOVETTER; Mark; MAUSS; Marcel; 1872-1950; economic sociology; encastrement; niveau d’intégration; sociologie économique

Law as the Interplay of Ideas, Institutions, and Interests: Using Polyani (and Foucault) to ask TWAIL Questions - Fakhri, Michael (International Community Law Review, 2008)
This paper sketches out some preliminary thoughts on political economy that stem from problematics that emerge from TWAIL. The TWAIL story of international law is one of frustration and disappointment because of the constant exploitation of the Third World despite all the historic changes in international legal ideas and institutions, but it also a story of hope in the moments of resistance. In order to better debate how particular international institutions should be changed or whether particular international institutions should be renounced, I suggest that we need to explicate the theories of political economy embedded within these institutions. Drawing from Karl Polanyi's The Great Transformation, bringing alongside the work of Michel Foucault, I sketch out one way of conducting a study of international political economy by suggesting that we can think of law as the interplay of ideas, institutions, and interests.
Law
Keywords: FOUCAULT; Michel; 1926-1984; TWAIL; economics; globalization; international agencies; international cooperation; international institutions; international law; international political economy; law

Etica e impresa: come e perché 'ritornare' a Polanyi - La Rosa, Michele (Business and Ethic: why should we go back to Polanyi?, 2008)
The essay, after trying to do a synthesis of today's debate about business and ethics, proposes to return to Karl Polanyi starting from a different meaning of the three founding principles proposed by the author (exchange, reciprocity and redistribution).
Sociology
Keywords: business ethics; business people; essay (literary form); professional ethics

Mercato: fatto o valore? Oltre la dicotomia - Rovelli, Riccardo (Market: fact or values? Beyond dichotomy!, 2008)
Economists are fond of proposing market solutions for many problems of resource allocation, while scholars from other social disciplines are often less inclined to adopt such solutions. In this essay I interpret the dichotomy for/against the market in the light of the one between neoclassical economics and the socio-anthropological tradition which originates with Karl Polanyi. In the first part, I suggest that this dichotomy runs in parallel to the one between facts and, which is typical of (neo)positivist thought. This dichotomy, which has been analyzed by Hilary Putnam, also reflects the self-portrait of neoclassical economics, as it has been proposed by Pareto and Robbins. Following this perspective in the second part I suggest on the one hand that the work of Polanyi should be interpreted as a reaction to neoclassical economics, but on the other hand it is also based on an incorrect interpretation of both facts and ideas in the history of ancient societies. Finally I notice that, although recent researches confirm that ancient societies should be interpreted as "conglomerations of interdependent markets" (thus following Temin against Polanyi and Finley), the presence and relevance of markets does not justify an under-socialized interpretation of ancient market economies: on the contrary, as it was well clear to many scholars, in a tradition that loosely connects Homer with Adam Smith, markets are and should be interpreted as value-laden facts. In the conclusion I discuss some implications of this view for the analysis of contemporary society.
Sociology
Keywords: PUTNAM; Hilary; 1926-2016; SMITH; Adam; 1723-1790; economists; feasibility studies; markets - social aspects; neoclassical economics; neoclassical school of economics; resource allocation

Karl Polanyi's The Great Transformation: perverse effects, protectionism and Gemeinschaft - Dale, Gareth (Economy and Society, 2008)
Drawing upon Karl Polanyi's journalistic writings and unpublished lectures from the 1920s and 1930s, this article reconstructs the lineaments of his research programme that was to assume its finished form in The Great Transformation. It identifies and corrects a common misinterpretation of the thesis of that book, and argues that Polanyi's basic theoretical framework is best conceived as Tönniesian: market society is Gesellschaft, while the ‘protective counter-movement’ of The Great Transformation is Gemeinschaft, understood dynamically. It examines the two central mechanisms by which, in Polanyi's understanding, Gesellschaft broke down in the mid-twentieth century: the ‘clash between democracy and capitalism’ and the ‘perverse effects’ whereby political intervention in markets impairs profitability and saps the vitality of the market system.
Political Science
Keywords: Ferdinand Tönnies; TONNIES; Ferdinand; 1855-1936; The Great Depression; capitalism; democracy; perverse effects doctrine

Karl Polanyi's Legacy - Hart, Keith (Development and Change, 2008)
Click on the article title to read more.
Anthropology; Development Studies
Keywords: biography

A New Alliance of De-legalisation and Legal Formalism? Reflections on Responses to the Social Deficit of the European Integration Project⋆ - Joerges, Christian (Law and Critique, 2008)
This paper will cover a wide range of issues. It will start with a reconstruction of the European Community’s ‘social deficit’, arguing that a credible response to this deficit would be a pre-condition for the democratic legitimacy of the deepened integration project. Such a response can be developed in a re-conceptualisation of European law as a new type of supranational/trans-statal conflict of laws – this is the thesis defended in the second section. This vision is contrasted in the third section, first with the steps towards Social Europe envisaged in the Draft Constitutional Treaty, and then with the messages of the recent judgments of the European Court of Justice (ECJ) in Viking and Laval. It goes without saying that the theoretical premises of the argument, let alone its many interdisciplinary dimensions and empirical background, can often only be signalled, but not developed systematically. " I wish to submit is that the ‘social embeddedness’ thesis can help us to understand why Europe has developed an ever more sophisticated regulatory machinery entrusted with the management of the internal market – and why the social deficit of the European construction has become a prominent part of the European agenda.
Law
Keywords: Social Europe; conflict of laws; ordoliberalism; social deficit; social embeddedness; socio-economic division; unity/diversity

La dépolitisation de la notion de « capital social » : pourquoi pas un retour à Karl Polanyi? - Bibeau, Gilles (Anthropologica, 2008)
Anthropology
Keywords: social capital

Društvo I (ili) Tržište – Sociološka Konceptualizacija Procesa Marketizacije Društva - Peračković, Krešimir (Gesellschaft und (oder) Markt. Eine soziologische Konzeptualisierung des Prozesses der Gesellschaftsmarketisierung., 2008)
The main goal of this work was to theoretically conceptualise the process of marketisation which designates the transformation of society into a market economy and social relations into market relations. The starting point is first the comparative analysis of the definitions of the term market by some classic authors (Smith, Marx, Weber, Durkheim and Parsons), each of whom define it from their perspective as a monetary mechanism of exchange in the economic sphere of social activity. In the second chapter K. Polanyi's theory of social transformation is presented, in which he is the first to state that the principle of market self-regulation has become the fundamental feature of modern society. Analysed in the third chapter is the market economy society model of D. Slater and F. Tonkiss, who claim that the process of marketisation in the most developed countries has already been completed and that today's society has already become a market society. The paper also presents in short the theory of marketing neglected in sociological literature, the main concept of market economy as a rational system of research and planning, which is currently not only applied in the economy but also in politics and culture. A special chapter is devoted to commodification, a process that concretises on a micro level the goals of marketisation, implying the transformation of nature, things, people, relations, meanings and immaterial resources into market commodities. The ultimate result of the marketisation and commmodification processes in a market society becomes evident in Rifkin's ominous hypothesis that all human life has become an experience to pay for, which is also the topic of the last chapter. (English)
Sociology
Keywords: Kommodifizierung; Marketisierung; Markt; Marktgesellschaft; Marktverhältnisse; capitalism; commodification; comparative studies; definitions; komodifikacija; market; market relations; market society; marketing; marketisation; marketizacija; research; socioeconomics; tržišni odnosi; tržišno društvo; tržište

"A Market Where We All Fit" Adult Education and the Fair Trade Movement - Sumner, Jennifer (Canadian Journal for the Study of Adult Education, 2008)
The global market continues to create the "great and permanent evils" so well outlined by Karl Polanyi in his book, The Great Transformatioit His description of the destructive effects of the emerging self-regulating market during the Industrial Revolution is reflected today in the ongoing erosion of social, environmental, and economic sustainability in both the North and the South. In this downward spiral of life parameters, fair trade opens up the possibility of a market where we all fit, not where we all ultimately fail. Adult education has a vital role to play in opening up spaces where fair trade can prosper and grow, thus contributing to a second great transformation to a more sustainable society.
Education
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; adult education - economic aspects; international trade; self-regulation of industries; unfair competition

Le capital et la question nationale - Maucourant, Jérôme; Tinel, Bruno (Actuel Marx, 2008)
Nations are the forms of political organization which peoples construct for themselves. It is a commonplace to state that globalization tends (for the better) towards the end of nations. However the history of capitalism shows that such a hypothesis is questionable. Globalization is merely a stage in the development of capitalism, which has always leaned on certain nations to secure its deployment: England in the past, the U.S. today. The real question is thus that of the hegemony of one nation over other nations and, ultimately, the question of democracy, the sovereignty of peoples in the face of capital.
Economics
Keywords: democracy; globalization

Standing Polanyi on His Head: The Basic Income Guarantee as a Response to the Commodification of Labor - Caputo, Richard K. (Race, Gender & Class, 2008)
This paper examines unconditional basic income schemes proposed by Philippe Van Parijs and by Ross Zucker in light of Karl Polanyi's analysis of the 1795 Speenhamland Law and of Esping-Andersen's use of decommodification as a signifier of social provisioning in welfare states. It discusses tradeoffs between productive advantages of market-based economies and dehumanizing disadvantages of commodified labor. Contemporary redistributive schemes such as those of Van Parijs and of Zucker extol the productive virtues of market economies well beyond what Polanyi, who advocated for subjecting markets to social purposes, would consider acceptable. Further, Van Parijs's and Zucker's basic income schemes extol capitalism, perhaps mistakenly, as a means of achieving a more egalitarian social order of which Polanyi would in all likelihood approve, if such economies functioned as portrayed and were properly implemented to de-commodify labor, that is at a level considered adequate and acceptable to the society in which one lives.
Policy Studies; Social Work
Keywords: Speenhamland Law; United States - economic policy - 2001-2009; basic income guarantee; capitalism; commodified labor; decommodification; economic conditions - United States - 2001-2009; income; labor; labour; market economies; market economy; policy studies; social welfare states

Michael and Karl Polanyi: Conflict and Convergence - Gulick, Walter (Political Science Reviewer, 2008)
The article focuses on social philosophers and brothers Michael and Karl Polanyi. Particular attention is given to Michael's political, economic, and social thoughts and how they compare to Karl's. The author wishes to illuminate Michael's social though through this comparative study. Topics include the brother's family background, Michael's early thought, and divergent paths.
Political Science
Keywords: POLANYI; Michael; 1891-1976; biography; comparative studies; social theory

The Great Transformation: The Double Movement in China - Shaoguang, Wang (boundary 2, 2008)
KM: Both the title and the subtitle of this essay are adopted from Karl Polanyi, who published his famous book The Great Transformation: The Political and Economic Origins of Our Time in 1944. More than six decades have passed since its publication, but, as Joseph E. Stiglitz states in the preface of the recent new reprint, “the issues and perspectives Polanyi raises have not lost their salience . . . it often seems as if Polanyi is speaking directly to present-day issues.” ... China is experiencing “a transformation unprecedented in thousands of years” (qiannian weiyou zhi da bianju). More than one hundred years ago, the Qing official Li Hongzhang used these words to describe the era he was living in. Two decades later, the May Fourth generation had a similar take on their time, too. However, in terms of the economic foundation and the speed, depth, and scope of the social structure’s transformation, no other era can be compared to the last two decades or so.
Political Science
Keywords: China; Great Transformation; The (Book); double movement

Is an Alternative Globalization Possible? - Evans, Peter (Politics & Society, 2008)
Building on Polanyi's concept of the “double-movement” through which society defends itself against domination by the self-regulating market, this article sets out some key organizational and ideological hurdles that the contemporary “movement of movements” must surmount to challenge the hegemony of neo-liberal globalization. After outlining neo-liberalism's failures, it makes an argument for the possibility of “counter-hegemonic globalization,” defined as a globally organized project of transformation aimed at replacing the dominant (hegemonic) global regime with one that maximizes democratic political control and makes the equitable development of human capabilities and environmental stewardship its priorities.
Sociology
Keywords: double movement; globalization; neoliberalism; social movements; transnational networks

Personal Retirement Accounts & the American Welfare State: A Study of Income Volatility and Socioeconomic Status as Correlates of PRA Support - Caputo, Richard K. (Journal of Poverty, 2008)
Based on a sample (n = 6,407) from the National Longitudinal Survey of Youth, 1979 cohort, this study found a sizable majority (69.1%) of support to replace a portion of Social Security with Private Retirement Accounts. Logistic regression analysis showed that SES was a robust predictor of PRA support, particularly for upper class vs. lower class respondents. Findings suggested that there may be less support for a major pillar of welfare state social provisioning, despite successful Congressional attempts to block related legislation to date, especially since the opinions of more affluent persons tend to have greater resonance with policymakers than those of lower income individuals.
Policy Studies; Social Work
Keywords: United States; employee fringe benefits; personal retirement accounts; policy studies; privatization; regression analysis; social security; socioeconomic status; socioeconomics; surveys; volatility (finance); welfare state

After the disaster - Hart, Keith (Anthropology Today, 2008)
Naomi Klein's The Shock Doctrine offers a weak analysis of ‘neoliberalism’ linked to a defeatist ideology. If we wish to move beyond the global economic crisis, we should borrow ideas from Mauss, Polanyi and Keynes; but the political level for an appropriate response is not obvious.
Anthropology
Keywords: KLEIN; Naomi; neoliberalism

Karl Polanyi for Historians: An Alternative Economic Narrative - Knowles, Rob; Owen, John R. (The European Legacy, 2008)
The purpose of this essay is to provide the historian with a generic understanding of the term economy by examining some aspects of the work of the Hungarian “economic historian” Karl Polanyi (1886–1964). It does not seek to explain Polanyi's economic ideas to economists nor does it seek to locate his ideas within the discourses of the academic discipline of economics; there is abundant academic literature which carries out those tasks. This essay is intended to help fill a void in the historical understanding, especially the modern historical understanding, of the term economy, and of how the characteristics associated with it are generally understood. Yet, in reality, it is the neoclassical paradigm of economics which is typically and uncritically taken to be the touchstone for understanding the economy. This circumstance is problematic, however, when referring to the economy of societies earlier than the late nineteenth century or of societies whose culture differs radically from that of the advanced capitalist “west.” Polanyi's insights may help historians avoid the risk of either distorting or anachronistically misunderstanding the economy of such societies.
History
Keywords: economic history; economic theory; history

Une révolution bureaucratique britannique ? - Gales, Patrick LE; Scott, Alan (Una revolución burocrática británica ? Autonomía sin control o « freer markets, more rules »., 2008)
This article originated with a puzzle : how best to account for changes in the behavior of groups, organizations and individuals in Great Britain ? A detailed analysts of what Weber and Polanyi identified as interdependencies between state and market, and of the state's role in creating the market, led to the decision to adapt the notion of bureaucratic revolution put forward by Weber. We argue that the British bureaucratic revolution is reflected in the fact that the state plays an essential role in social change by creating rules and institutions that lastingly orient actors' behavior. The examples of health and local authorities are then used to identify mechanisms that were influential throughout a ten-year period specifically the introduction of competition features (rewards and punishments) and of auditing and inspection. If our interpretation is accurate, the effects of this bureaucratic revolution may well come to be felt in contexts other than Great Britain. (English)
Sociology; Political Science
Keywords: 1997-2010; Great Britain - social conditions - 1945-; WEBER; Max; 1864-1920; bureaucratization; economic policy; social goals; socioeconomics

Tall among the trees: Organizing against globalist forestry in rural British Columbia - Prudham, Scott (Journal of Rural Studies, 2008)
In January of 2001, the TimberWest Corporation permanently closed its Youbou sawmill facility near Duncan, British Columbia, Canada laying off 220 workers. On the surface, the Youbou mill closure reinforced a pervasive sense that workers and communities in the province are increasingly vulnerable to an ever more globally integrated and footloose forest industry. But a funny thing happened in Youbou; the workers fought back. While the mill was completely dismantled and scrapped, with no discernable response from the provincial government, workers from the Youbou sawmill banded together to form a new NGO called the Youbou TimberLess Society. Since its inception, the YTS has developed into one of the most unique and compelling voices for forest policy reform in BC. In so doing, the YTS also represents something of an anomaly in exhibiting many of the characteristics of so-called new social movements, and yet emerging from the industrial working class. This paper explores the ways in which the YTS has served as a powerful arena in which the subjectivities of sawmill workers and other community members have been transformed through organized resistance to global capital. At the same time, informed by the YTS, the paper draws on Polanyi's idea of the dual movement to examine scales and terms on which globalization and competing notions of autonomy are contested in moral economies of both work and nature. Copyright (c) 2008 Elsevier Ltd.
Geography
Keywords: Canada; activists; double movement; employees - Canada; forest policy; forest policy - Canada; forest products industry; forests and forestry; lumber industry - British Columbia; lumber industry - Canada; rural studies; social movements; social movements - Canada

Rationality as a Social Construction: What Does Individual Behavior Have To Say About Development in an Amazon Community? - Gramajo, Andrés Marroquín (Journal of Economic Issues (Association for Evolutionary Economics), 2008)
This article argues that two different manifestations of rational behavior can coexist and collide in a relatively homogeneous society. In the Ticuna community of Arara in the Colombian Amazon; on the one hand, the majority of villagers tend to reach relatively lower levels of material wealth, following Polanyi's idea of the pre-modern man (1968a; 1968b; 1968c), and also Sahlins' (1972) idea of the original affluent man. On the other hand, community leaders and schoolteachers tend to accumulate material wealth, following Polanyi's idea of modern-man (1968a; 1968b). These behavioral frameworks help explain the limited success of certain types of development programs in the Ticuna community.
Economics
Keywords: Amazon River Region; Colombia; Tucuna (South American people); behavioral economics; communication in economic development; economic development; economic policy; economics - moral & ethical aspects; pre-modern man; rationality; reason; saving and investment; statics & dynamics (social sciences); wealth

The market and the nation: Austrian (dis)agreements - Karner, Christian (Social Identities, 2008)
This article relates contemporary Austria's much-discussed and internally contested identity politics to transnational socio-economic transformations and their far-reaching local/national effects. A qualitative analysis of (wide-ranging contributions to) current debates on the environment, food production, climate change, social inequality and welfare, higher education, art, migration, and unemployment reveals a recurring pre-occupation with expanding/encroaching markets, their advocated limits, assumed costs or promises. The negotiation of national identities is shown to unfold in relation to three inter-related phenomena: first, widening commodification; second, what Karl Polanyi termed the 'double-movement' between 'dis-embedded' economics and political counter-assertions; third, competing ideological visions of the relationship between economic activity/market forces and social order, group boundaries, solidarities and hence exclusions/inclusions.
Sociology
Keywords: Austria; commodification; economic anthropology; globalization; identity politics; markets; migration; nationalism; political science; public contracts; qualitative research; social order; socioeconomics

Going Global: The Transnational Politics of the Dalit Movement - Smith, Peter (Globalizations, 2008)
This article analyses the involvement of the Dalits (formerly 'untouchables') in the World Social Forum (WSF) processes. The focus will be on one networked organization in particular, the National Campaign for Dalit Human Rights (NCDHR) as a key organization which served as a catalyst for linking the Dalit struggle against neoliberal globalization and casteism with the social forum process and the global justice movement. The article argues that the Dalit struggle, domestically and internationally, can best be understood from a Polanyian perspective, as a countermovement for social protection against neoliberal globalization. It examines the dialectic of globalization within an Indian context first in terms of the impact of neoliberal globalization upon the Dalit community and then the NCDHR's decision to go global, to the WSF. In taking their cause beyond India, a central focus of Dalit activity remains rooted in making the Indian state serve as a means of social protection for the Dalit peoples. Este artículo analiza la participación de los Dalits (previamente llamados "intocables") en los procesos del Foro Social Mundial (WSF, por sus siglas en inglés). El enfoque se concentrará particularmente en una organización en red, la Campaña Nacional por los Derechos Humanos de los Dalits (NCDHR, por sus siglas en inglés) como una organización clave que sirvió como catalizadora por haber enlazado la lucha de los Dalits contra la globalización neoliberal y el casteísmo, con el proceso del foro social y el movimiento de justicia global. El artículo plantea que la lucha de los Dalits, tanto doméstica como internacionalmente, puede entenderse mejor desde una perspectiva polanyana, como un contramovimiento para la protección social en contra de la globalización neoliberal. El mismo examina la dialéctica de la globalización dentro del contexto indio, primero en términos del impacto de la globalización neoliberal sobre la comunidad de los Dalits y luego, en términos de la decisión de la Campaña Nacional por los Derechos Humanos de los Dalits (NCDHR) de tomar una dirección global, hacia el Foro Social Mundial. Al llevar su causa más allá de la India, el tema central sobre la actividad de los Dalits permanece arraigado obligando al estado indio a servir como un medio de protección social para los Dalits.
Political Science
Keywords: Dalits; class politics; countermovement; globalization - social aspects; human rights; international relations

Weber, Polanyi, and Finley - Tompkins, Daniel P. (History and Theory, 2008)
KM: a review article on Nafissi's book.
History
Keywords: WEBER; Max; 1864-1920; biography; review

Beyond Ethnic Entrepreneurship: An Embedded Market Approach to Group Affiliation in American Enterprise - Valdez, Zulema (Race, Gender & Class, 2008)
The traditional ethnic entrepreneurship paradigm suggests that resource mobilization based on ethnic group membership and the particular structural conditions of the economy and society combine to facilitate ethnic enterprise. Yet, this model remains largely descriptive and imprecise with respect to how and why class and ethnic resources and structural opportunity matter. Furthermore, this approach neglects to consider the likelihood that other non-ethnic social groupings distinct from ethnicity, such as those rooted in class, gender, or racial group affiliation, might also influence entrepreneurship. To address these concerns, this article introduces an "embedded market" (Block, 2003; Polanyi, 1944) approach that situates the role of group affiliation within the context of American capitalism. This approach begins with the premise that the role of group affiliation in economic action originates in and is maintained and reproduced by the social structure of the capitalist system in which it is embedded. Specifically, the embedded market approach reconsiders ethnic group membership, along with other politically-influenced social groupings (e.g. class, gender, nativity, and race) as non-essential relationships of reciprocity. In this conception, group affiliation provides the basis for compensatory relief in the form of social capital to augment market uncertainty in the modern market economy. This article uses the case of Latina domésticas to demonstrate the compensatory role of group affiliation and its corollary social capital in facilitating ethnic and "non-ethnic" enterprise in American capitalism.
Sociology
Keywords: United States; business enterprises - United States; capitalism; class; doméstica; embedded market; entrepreneurship; ethnic entrepreneurship; ethnic groups; gender; race; social capital; social classes

Karl Polanyi and the antinomies of embeddedness - Gemici, Kurtuluş (Socio-Economic Review, 2008)
While Polanyi argues that all economies are embedded and enmeshed in social relations and institutions, he tends to see market economy as disembedded, which reveals a tension in his thought. The main motivation for this paper is to understand the origins of this tension. On the basis of a systematic formulation of Polanyi's work, it is argued that Polanyi employs embeddedness in a dual manner: (a) as a methodological principle akin to methodological holism, and (b) as a theoretical proposition on the changing place of economy in society. These two formulations of embeddedness contradict each other. After tracing out the origins of this contradiction, this paper concludes by considering the implications of this analysis for economic sociology. It is argued that embeddedness as a methodological principle is the only acceptable usage of the term. Yet, in this capacity, embeddedness falls short of economic sociology's goal of providing a theoretical alternative to neoclassical economics.
Sociology; Anthropology
Keywords: Austrian history of economic thought; cultural economics; economic anthropology; economic sociology; economic systems; embeddedness; evolutionary; historical; institutional; relation of economics to other disciplines

Nano-worlds as Schumpeterian emergence and Polanyian double-movements - Randles, Sally; Dewick, Paul; Loveridge, Denis; Schmidt, Jan C. (Technology Analysis & Strategic Management, 2008)
The overarching question raised in this special issue is whether societies can, do or indeed should steer new and emergent science and technological development and its management on to trajectories construed as more or less 'desirable'. It therefore sits at the interface of two arenas. These are governance: processes of shaping/steering emergent technologies and markets; and sustainability: normative agendas incorporating a range of potentially competing conjectures and internally inconsistent desires such as to facilitate rather than stifle innovation, to enable economic development, to anticipate or deploy strategies to cope with risk and uncertainty, and to encourage technological developments that benefit rather than harm humans, their quality of life and the natural environment. Despite the potential for apparent empirical inconsistencies and contradictions that manifest as outcomes of the negotiation of these aims, there is (pace Karl Polanyi) a normative entry point to all of the articles and the material they draw upon, which is the idea that markets and technologies should be the handmaiden of societies, not vice versa. It is now widely recognized that 'nanotechnology' is a diverse set of feasible procedures emerging from scientific possibilities to enable the production of artefacts at the nanoscale creating new products, processes and services. Attention has to be paid to the desirability of these artefacts, which involve social, economic, ecologic, political and ethical matters that surround their emergence. The purpose of this special issue is to set out the current and future prospects for the widespread use (or innovation) of technological convergence at the nanoscale to create nano-artefacts, and the needs for governance and regulation that will accompany these innovations.
Sociology; Science and Technology Studies
Keywords: POLANYI; Karl; 1886-1964; SCHUMPETER; Joseph Alois; 1883-1950; double movement; economic development; editorials; emergence; governance; nano-; nanotechnology; new product development; quality of life; sustainability; technological innovations

Karl Polanyi's and Karl William Kapp's Substantive Economics: Important Insights from the Kapp—Polanyi Correspondence - Berger, Sebastian (Review of Social Economy, 2008)
Based on the unpublished Kapp-Polanyi correspondence, the paper analyzes the relationship between the two economists, as well as the meaning and origin of substantive economics, i.e. one of the key concepts of institutional economics with distinctly European roots. The correspondence shows how both economists influenced each other in their similar understanding of the substantive economy, and reveals that these similarities and the mutual influence date back to the 'planning debate' of the 1920s and 1930s. The documents also evidence the importance of Carl Menger's definition of substantive economics in the posthumous and untranslated second edition of the Grundsätze der Volkswirtschaftslehre (Principles of Economics) (1923). As a result, Kapp's political economy, i.e. his social minima approach appears in new light. The latter actualizes the full potential of substantive economics for a modern political economy by integrating insights from Polanyi's substantive economics, Menger's differentiation of human needs according to their urgency, and Max Weber's substantive rationality.
Economics
Keywords: KAPP; Karl William; environmental management; social economy; substantive economics

Karl Polanyi y el Problema De Los Mercados - Colombo, Octavio (Studia historica., 2008)
The purpose of this work is to analyze the Karl Polanyi’s conceptions about the pre-capitalist-markets, especially his revision of the categories of trade, money and market. In first place, we present a critical examination of the fundamental ideas of The Great Transformation, where his later reflections about pre-industrial societies are ground. Using some basic categories of the critique of political economy, we treat to show certain methodological and conceptual limits of his proposal. Then, we analyze the Polanyi’s ideas related to the features of pre-capitalist markets. We conclude that, even when the polanyian categories and reasoning need a deep revision, his merit is to propose a really historical approach about the markets; approach that until now has not received a suitable attention.
History
Keywords: Great Transformation; The (Book); critique; great transformation; pre-capitalist markets; preindustrial society

Reciprocity, Exchange and Redistribution. An experimental investigation inspired by Karl Polanyi’s The Economy as Instituted Process - Danese, Giuseppe; Mittone, Luigi (MyScienceWork, 2008)
Inspired by Karl Polanyi’s writings on three allocation modes, namely reciprocity, exchange and redistribution, we first tested a reciprocity ring with ten players. The baseline treatment, with no possibility of socialisation, displayed very low levels of allocative efficiency. Consistently with the Polanyian approach to reciprocity, we found that inducing the notion of symmetry among the players increased efficiency levels significantly. We then simulated a market exchange, with significant allocative efficiency gains. We conclude that indirect-reciprocity rings among anonymous players can seldom function in the absence of definite institutional refinements, promoting forms of symmetry-acknowledgement.
Political Science
Keywords: instituted economic process; reciprocity

L'innovation sociale dans les services d'aide a domicile. Les apports d'une lecture polanyienne et feministe. (With English summary.) - Degavre, Florence; Nyssens, Marthe (Revue Francaise de Socio-economie, 2008)
The aim of this contribution is to analyze the dynamic of social innovation of home-care services. Based on the works of Polanyi which analyse socio-economic dynamics and on feminist theories in the field of care, we develop an original grid of analysis developing criteria to grasp the processes of social innovation and to highlight the peculiarities of gender relationships at stake in these services. We also suggest normative criteria to evaluate the quality of social innovation. We apply this conceptual framework to the empirical field of new home-care services, which have emerged 20 years ago, and provided to elderly dependents in Wallonia.
Interdisciplanary
Keywords: economics of the elderly; economics of the handicapped; feminist economics; health; non-labor market discrimination; non-labour market discrimination; personal; professional; and business services; social innovation

Labour and the Transformation of East Asian Capitalism: A Regional View - Gray, Kevin (Conference Papers – International Studies Association, 2008)
Two of the most salient aspects of the recent shift towards financialisation and neoliberal restructuring since the 1970s have been the restructuring of global production towards China, and the growing threat to workersâ livelihoods posed by increased capital mobility. Both of these trends can be seen as capitalâs response to the crisis of profitability that has arisen from the unsustainable global social accord between workers and capital that was inherent in post-War US hegemony. Transnational manufacturing capital sought ever cheaper sites of cheaper and non-unionised labour, whilst there was at the same time a tendency for capital to withdraw from productive investment altogether and enter the financial market. This paper will seek to explore the implications of these developments for the working classes of East Asia as a region, and will take examine the present transformations from the perspective of Polanyi's depiction of social responses to earlier periods of financialisation. The emergence of China as the 'workshop of the world' has had profound effects on working classes in the rest of East Asia, and have changed the parameters within which political challenges can be mobilized. Similarly, the viability of the recent restructuring of the East Asian regional political economy is highly contingent upon how working class movements develop in China, and whether China can continue to act as a "spatial fix". Through an examination of the empirical evidence on what kind of strategies are being adopted by labour movements within the East Asian countries, the paper will attempt to adopt an explicitly regional view of the transformations of regional capitalism which overcomes the limitations of national-level analyses. ..PAT.-Unpublished Manuscript
Political Science; International Relations
Keywords: East Asia; capitalism; economic conditions in East Asia; economic structure; financialization; international economic relations; international trade

The Space of Rights: On Benjamin, Gramsci, and Polanyi - Holub, Renate (Conference Papers – International Studies Association, 2008)
For intellectual generations born at the end of the 19th century in Europe, the discourses on rights were to a large measure determined by proponents and detractors of various versions of Marxism. Hence the debates on justice and rights predominantly operated with the conceptual and analytical instruments of European political economy. These debates also were premised on assumptions about the status of the political economy of Europe and North America in the distribution of global space. But the intellectual generations born at the end of the 19th century, and particularly those with interests in the Marxist project – as Benjamin, Gramsci, and Polanyi were– were also witnesses to the facts of the Soviet Revolution and its evolution into the Stalinist state. In this paper I will first of all examine the ways in which Walter Benjamin, Antonio Gramsci, and Karl Polanyi elaborated and expanded the concept of transatlantic space inscribed into the Marxist project. I will then investigate to which extent their familiarity with the rights practices of Stalinism impacted their elaboration of new forms of the space of rights: Benjaminâs concept of the historical space of âmessianismâ that transcends the historical limits of the space of rights of historical materialism; Gramsciâs concept of cultural space as a struggle for rights that expands Marxâs terrain of political economy, and Polanyiâs concept of anthropological space that expands the conceptual space of economic analysis of classical Marxism. The purpose of the paper is to gain a measure of understanding of the links that obtain between conceptual apparatuses of leading intellectuals and global transformations in the first half of the twentieth century, particularly since these intellectuals developed their ideas relatively independently from the structures of organized knowledge production of universities and academies. ..PAT.-Unpublished Manuscript
Political Science
Keywords: BENJAMIN; Walter; 1892-1940; GRAMSCI; Antonio; 1891-1937; communism; human rights; political science

Transformations, Then and Now: The Appeal of Karl Polanyi - Karnik, Ajit (Economic and Political Weekly, 2008)
Karl Polanyi's views on the nature of "pre-market" society are influential not only among historians but also among economists concerned with present-day transitional and developing economies. This paper examines Polanyi's arguments about the "Great Transformation" from traditional to market society in the light of recent advances in economic theory and empirical evidence from a range of European and non-European societies. These theoretical and empirical considerations provide little support for Polanyi's views concerning fundamental discontinuities between traditional and market societies. The paper concludes that Polanyi's rosy view of pre-market society provides an inappropriate historical basis for addressing the challenges faced by present-day transitional and developing economies.
Economics
Keywords: critique; economic history; market economies; market economy; market mechanism; market mechanisms; money; peasant class; pre-market society; transitional economies

Movements of the World Unite! Assessing Prospects for Social Movement Unionism in Canada - MacArthur, Julie (Conference Papers – International Studies Association, 2008)
Within the field of critical political economy exists a literature urging a re-conceptualization of democracy (Munck 2002, Cox 1997, Webster and Adler 1998). Liberal, particularly neo-liberal, political systems are critiqued for their binary separation of economics and politics leading to substantive disenfranchisement and elitest governance. Robert Cox (1997) has called this âlimited democracyâ and argues that consumer choice and infrequent elections cannot be equated with democratic citizenship. One theorized response to this problem builds on the work of Karl Polanyi (1944) and his concepts of âembeddednessâ and the âdouble movementâ. Democracy can be deepened and strengthened by asserting social control over the economy and society at multiple levels and across issue areas. This is accomplished by a movement of social forces forcing a re-embedding in response to periods of increasing economic and elite consolidation. A problem in this literature has consistently been the agent or agents of change.This paper critically explores the argument that Social Movement Unionism (SMU), the organizational and theoretical blend of trade unionism and social movements, can and may serve as the agent of a Polanyian double movement in Canada. While theorists of SMU argue that labour necessarily needs to branch out laterally as a response to neo-liberal policies, I explore the tensions between âoldâ labour and contemporary social movements in Canada, such as the environmental movement. I ask: to what extent is organized labour taking on issues beyond their narrow collective-bargaining interests? Is there significant personnel overlap between labour and social movement organizations such as environmental, womenâs or anti-war groups? In answering these questions I intend to draw out the tensions between various actors these theories look to for change and assess their relevance in the Canadian context. By bringing together literature on transnational social movements, labour studies, political economy and international relations this paper takes an interdisciplinary approach to understanding these challenges. ..PAT.-Unpublished Manuscript
Political Science
Keywords: Canada; democracy; economics; elite (social sciences); political science

Polanyi's Double Movement: A Critical Reappraisal - Maertens, Eppo (Social Thought & Research, 2008)
The article offers a critical reappraisal of Karl Polanyi's claim that the restructuring of the economy based on the ideals of the self-regulating market inevitably leads society to reassert itself against the commodification of land, labour and money. Dubbed as the "double movement," the author focuses his reappraisal on the two aspects of the movement. The first refers to the push for free market reforms by various groups in society, and the second refers to the counter-movements that he argues necessarily and spontaneously mobilize against it. In this paper, he argues that the first aspect is an area that deserves further attention, both from those who wish to apply his ideas as well as from those who wish to challenge them.
Sociology
Keywords: central economic planning; commodification; critique; double movement; dual economy; economic structure; free enterprise; market ideology; markets; public welfare

The Great Transformation: The Political and Economic Origins of Our Time - Meier, Brian (Social Thought & Research, 2008)
The article reviews the book "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polayni.
Sociology
Keywords: Great Transformation; The (Book); book review; economics; nonfiction

KARL POLANYI ABOUT INSTITUTED PROCESS OF ECONOMIC DEMOCRATIZATION AND SOCIAL LEARNING - Mendell, Marguerite (PEKEA Newsletter N° 14, April – June 2008 / ResearchGate, 2008)
This text will not focus on The Great Transformation but will deal with previous and following writings from Karl Polanyi where his emphasis is on the constitutive elements that define us as social beings and as agents of social change.
Economics; Political Science
Keywords: Great Transformation; The (Book); economic democratization; education; instituted economic process; social learning

In the Zone: Street Markets and Street Merchants in Socio-Legal Perspective - Morales, Alfonso (Conference Papers – Law & Society, 2008)
Typically when we think of street markets we think of chaotic places full of energy and vibrating with danger and opportunity. Traders or governments create markets to meet existing and emergent demands as well as the unintended consequences of other policy decisions. It is this institutional design, this governance, this regulatory process that provides access to the market and organizes the vending space therein. Public and private entities operating in fiscally constrained environments should attend to the variety of ways there are to establish and regulate markets. Municipalities typically assume that a detailed management scheme is the best approach to managing access to markets and organizing the distribution of space, the assumption being that chaos would result in the absence of the state. However, this is not necessarily the case, merchants' can self-organize access to space as well as a stable and flexible spatial order, and this self-organization can minimize costs, improve access, and contribute to social goods and goals associated with having a public market.This article provides an empirical justification for this claim by examining the creation of Chicago's Maxwell Street Market (hereafter the Market), and describing the subsequent changes in the regulatory scheme of that Market. This discussion recalls Polanyi's observation that all markets are regulated, one way or another, but that the forms and character of regulation obviously varies – and thus this article argues the thesis that even in apparently unregulated markets we will find regulation, self-created, that produces a social order, in this case a stable and flexible order that accommodates a variety of private and public circumstances and goals. Our case is Chicago's Maxwell St. Market, which between 1973 and 1994 resembled unfettered capitalism. An ethnically heterogeneous multitude of street entrepreneurs organized vending space with little violence in the absence of stable, state sponsored, legal expectations. But this self-organization is nested in an overall history of unregulated street commerce in the area, starting in the 1870s, followed by the City government's creation and regulation of the Market in 1912, then a period of regulation lasting 60 years, followed by a radical change in the regulatory regime that produced a self-organized Market for about 20 years, then finally the City recaptured the Market and has regulated it again since 1994. Planners and policy makers will find this case interesting for three reasons: first, it is an interesting history of public markets and planning interests, second, the data indicate how an ethnically heterogeneous population can self-produce a flexible and stable social order and third, planners and policy makers concerned with locally appropriate and economically efficient, combinations of government and self-regulation of economic activities might apply lessons from this case to the large and growing interest in public markets around the country. ..PAT.-Unpublished Manuscript
Law; Urban Studies
Keywords: government regulation; markets; municipal government; nation-state; policy sciences

Economie et Rationalite: Apports et limites de l'approche polanyienne. (Economics and Rationality: Contributions and Limits of Polanyian Approach. With English summary.) - Postel, Nicola; Sobel, Richard (Cahiers d'Economie Politique, 2008)
Polanyi analyzes the historical deployment of a "formal" economic science starting from the triptych "market-rarety-instrumental rationality". It reveals this triptych, and the knowledge which is devoted to it, as being a part of a question broader than should analyze a "substantial" economic science being interested in the triptych "need-nature-institution". If we can and must follow Polanyi in his criticism of economism suited to the first triptytic, we have more reserve to accept his solution of substitution, an heterogeneous mixture of naturalism and institutionalism, of essentialism and historicism. The thesis defended in the article is that it is necessary to be more Polanyian that Polanyi himself, and to develop an economy of the practical reason, base of an economic science reintroduced inside social sciences.
Sociology; Economics
Keywords: criticism of economism; formal economy; general economics

Third Way Labor Law Reform in Chile - Rosado Marzan, Cesar F. (Conference Papers – Law & Society, 2008)
Latin America is currently undergoing Karl Polanyi's "double movement" at full swing, as most governments of the region are currently experimenting with policies that defy the neoliberal orthodoxy that has been reigning there for almost three decades. One of such governments has been the center-left Concertación governments of Chile, which have been elected since the restoration of democracy in 1990. In addition to poverty alleviation programs, Concertación has been in an ongoing process of reforming the country's labor laws, attempting to restore some of the labor rights existing prior to the 1973 coup, as well as creating new rights and institutions. The labor inspectorate has been strengthened and reformed under the framework of "Latin" systems of labor inspections, which are pedagogical rather than punitive in orientation. Labor courts are also being radically bolstered, providing workers with a renewed legal avenue to enforce their rights. Although the reforms fall short of full restoration of trade union rights, namely national collective bargaining, they do point to a clear break with the "stateless" regulatory, neoliberal model that Chile was once associated with and provide symbolic and intellectual fodder for further reforms in the country and beyond. ..PAT.-Unpublished Manuscript
Law; Sociology
Keywords: Chile; Latin America; labor laws & legislation; labour laws & legislation; law reform; mixed economy

Group Affiliation and Market Embeddedness in American Enterprise - Valdez, Zulema (Conference Papers – American Sociological Association, 2008)
In this article, Polanyi's (1944) notion of society as constituted by three forms of economic integration (market exchange, reciprocity, and redistribution) is applied to entrepreneurship. In advanced capitalism, the market-exchange relationship is the dominant form of economic integration; secondary relationships of reciprocity and redistribution, however, co-exist alongside relations of market exchange. Following Polanyi (1944), this article introduces an "embedded market" approach to enterprise. The embedded market approach considers the differential effects of primary and secondary relationships on entrepreneurial outcomes. The traditional ethnic entrepreneurship paradigm suggests that resource mobilization based on ethnic group membership is essential for entrepreneurial success, as measured by participation and earnings. The embedded market approach reconsiders ethnic group membership, along with other politically-influenced human social groupings (e.g. class, gender, nativity, and race) as non-essential relationships of reciprocity. In this conception, group affiliation provides the basis for compensatory relief from market uncertainty in the form of social capital. Ultimately, the embedded market approach provides a systematic and comprehensive approach to understanding the role of group affiliation in facilitating ethnic and "non-ethnic" enterprise in America.
Sociology
Keywords: Latino/a Sociology; United States; class and gender; commercial policy; entrepreneurship; ethnic entrepreneurship; inequality; international economic integration; new business enterprises; race

Double Movement in China - Wang, Shaoguang (Economic and Political Weekly, 2008)
This paper traces China's move towards a market economy in the mid-1980s, the near triumph of market forces in the 1990s, and the countermovement this engendered as inequalities between the rich and poor increased and social security networks collapsed. It focuses on the country's regional and healthcare policies to illustrate how it has dealt with issues of inequality and insecurity over time. The prevailing view now is that the market is necessary but it must be embedded in society. And the state must play an active role in the market economy to prevent a disembedded and self-regulating market economy from dominating society.
Political Science
Keywords: China; double movement; market economy